Montong Durian Farmers' Behavior in Control of Bangkalan Disease in Parigi Moutong Regency, Central Sulawesi - Jaya, Kasman; Ratnawati, Ratnawati; Sudewi, Sri; Spetriani, Spetriani (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The presence of bangkalan disease has proven detrimental to Montong durian farmers in Parigi Moutong. Various control efforts have been made but have yielded no significant results. This study aims to determine the behavior of Montong durian farmers in controlling the attack of bangkalan disease. The study was conducted in Parigi Moutong Regency, Central Sulawesi, specifically in Tolai Village (Torue District), Buranga Village (Ampibabo District), and Sumber Sari Village (South Parigi District), using quantitative methods and survey techniques with structured questionnaires and in-depth interviews involving 10 farmers from each village, totaling 30 respondents. The findings indicate that farmers’ knowledge about the causes of bangkalan disease falls into the low category. Adequate levels of education and years of farming experience have not provided effective solutions to overcome the problem. Farmers generally expressed dissatisfaction with pesticide-based control methods, even though they have had to increase both the frequency and dosage of application. Because the causative agent of bangkalan disease has not yet been identified, many Montong durian farmers have chosen to cease treatment and harvesting, as the risk of loss is too great. This phenomenon reflects a strong relationship between uncontrollable biotic factors and the social as well as psychological dynamics of the farmers. Plant diseases not only threaten productivity but also erode farmers’ hopes for successful harvests. Consequently, their impacts extend to the behavioral and mental well-being of Montong durian farmers, which may eventually endanger the sustainability of the agricultural production system in affected regions—in this case, the future potential of Montong durian cultivation in Parigi Moutong Regency.